Paradoxes of modernization unintended consequences of public policy reform - Margetts, Helen; 6, Perri, 1960-; Hood, Christopher, 1947- (Oxford : Oxford University Press, 2010)
'Paradoxes of Modernization' explores the unintended and unanticipated effects associated with 'modernisation' projects and tackles the key question that they provoke - why do policy-makers persist in such enterprises in the face of evidence that they tend to fail?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Policy sciences